2003
DOI: 10.1016/s0168-8278(02)00456-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α (TNF-α)-induced RANTES chemokine expression via activation of NF-κB and p38 MAP kinase: roles of TNF-α in alcoholic liver diseases

Abstract: Background/Aims: Increased concentration of plasma TNF-correlates with the clinical course of alcoholic liver diseases. In addition, hepatic RANTES which migrates CD4 T lymphocytes to liver is increased in patients with alcoholic hepatitis. We investigated that roles of TNF -on RANTES expression in hepatocytes.Methods: HLE cells were treated with TNF-in the presence, or absence of several inhibitors. Enzyme-linked immunoassay and reverse transcriptase-polymerase chain reaction were performed for the measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…RANTES has been proposed as a major mediator of antigen-independent T lymphocyte activation and has been found expressed in T cells, macrophages, fibroblasts, vascular smooth muscle, endothelial cells, renal mesangial (30), and tubular epithelial cells (21). TNF-␣ can also transcriptionally stimulate RANTES expression via activation of NF-B and p38 MAP kinase (23). Our studies also showed for the first time that mRNA levels of chemokine receptors CCR1 and CCR5 mRNA were upregulated by cisplatin.…”
Section: Role Of Inflammation In Cisplatin-induced Injurysupporting
confidence: 66%
“…RANTES has been proposed as a major mediator of antigen-independent T lymphocyte activation and has been found expressed in T cells, macrophages, fibroblasts, vascular smooth muscle, endothelial cells, renal mesangial (30), and tubular epithelial cells (21). TNF-␣ can also transcriptionally stimulate RANTES expression via activation of NF-B and p38 MAP kinase (23). Our studies also showed for the first time that mRNA levels of chemokine receptors CCR1 and CCR5 mRNA were upregulated by cisplatin.…”
Section: Role Of Inflammation In Cisplatin-induced Injurysupporting
confidence: 66%
“…Although the expression of RANTES was first thought to be limited to active T cells, recent data have shown that it is produced by a variety of tissue types in response to specific stimuli. RANTES mRNA is expressed late (3-5 d) after activation of resting T cells, whereas in fibroblasts, renal epithelial, and mesangial cells, RANTES mRNA is quickly up-regulated by TNF-␣ stimulation (Hirano et al 2003;Ogura et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, chronic ethanol consumption is characterized by an increase in the expression of a number of inflammatory cytokines. TNFa-induced protein and mRNA expression of RANTES in human hepatoma cells, possibly suggests that TNF plays a pivotal role in migration of inflammatory cells by RANTES to the liver in patients with alcoholic liver disease (30).…”
Section: Discussionmentioning
confidence: 99%